The Role of Artificial Intelligence (AI) in the Transformation of 21st Century Education - Afril, Rezkya; Rehani, Rehani; husna, Ilya (Journal Cerdas Mahasiswa, 2024)
The current technological advancements, particularly artificial intelligence (AI), have revolutionized the way education is conducted. AI not only changes the methods of teaching and learning but also creates new opportunities to enhance efficiency and personalize learning. This research aims to 1) formulate the understanding of AI in the transformation of education, 2) investigate the role played by artificial intelligence in the 21st-century education transformation, 3) explore its benefits, challenges, and implications. The research utilizes the Library Research method with content analysis techniques from various literature sources. The findings reveal that 1) AI in educational transformation is an artificial intelligence program within the educational system used in the planning, implementation, and evaluation of overall learning activities conducted. 2) AI plays a transformative role in education, altering the paradigm of teaching and learning by introducing significant innovations. 3) The use of artificial intelligence (AI) in education provides significant benefits such as personalized learning, increased efficiency, and accessibility. However, challenges related to privacy, ethics, technological gaps, and teacher training need to be addressed. The implications of AI use include better career preparation for students, innovation in education, and the development of learning independence. By understanding its benefits, challenges, and implications, educators can prepare students tobecome skilled and competitive future leaders in the digital era.